7+3t-5=7t+10-3t

Simple and best practice solution for 7+3t-5=7t+10-3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3t-5=7t+10-3t equation:


Simplifying
7 + 3t + -5 = 7t + 10 + -3t

Reorder the terms:
7 + -5 + 3t = 7t + 10 + -3t

Combine like terms: 7 + -5 = 2
2 + 3t = 7t + 10 + -3t

Reorder the terms:
2 + 3t = 10 + 7t + -3t

Combine like terms: 7t + -3t = 4t
2 + 3t = 10 + 4t

Solving
2 + 3t = 10 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
2 + 3t + -4t = 10 + 4t + -4t

Combine like terms: 3t + -4t = -1t
2 + -1t = 10 + 4t + -4t

Combine like terms: 4t + -4t = 0
2 + -1t = 10 + 0
2 + -1t = 10

Add '-2' to each side of the equation.
2 + -2 + -1t = 10 + -2

Combine like terms: 2 + -2 = 0
0 + -1t = 10 + -2
-1t = 10 + -2

Combine like terms: 10 + -2 = 8
-1t = 8

Divide each side by '-1'.
t = -8

Simplifying
t = -8

See similar equations:

| 5+8+-13= | | 1.5x=15.17 | | 180=(x+3)+(2x-61) | | x-4.72=5.28 | | 7(t-4)+8t=5(3t+3)-11 | | 27-55= | | 3n^4-33n^2+30= | | 9-6x=63 | | 6/5y=8 | | 4x^2-12x-40= | | 2b-3.4/06=-29 | | 5x^2-22x+8= | | -2(3s-3)-6=-2(5s+10)-3 | | 17-29x=4(-13-5x) | | 11/5y=8 | | 9r=4(r-10) | | y=2x+34 | | 5x*4x=35+7 | | x^2-44x+363=0 | | (x-8)(5x+7)=0 | | 27-11x=17x-33 | | x-.14(x)=305.00 | | -1(-12x-4)+4=-4(-3x+2)+16 | | 5*4=35+7 | | x^2+55-104=0 | | -9(-4m+8)-6m= | | x-.10(x)=305 | | 20x^2-33x-27=0 | | 3(7.5z-4)=18.5-5.5z | | 8-3h=5h | | 4/5x-10=7/10 | | -6n+8(2n-5)= |

Equations solver categories